Features processing with a cup metal cutting tools a limps shafts - Мелконов, Леонід Дмитрович (Eastern-European Journal of Enterprise Technologies, 2013)
The article presents the most advantageous method of cutting and orientation of the cup-tip tool relatively to the processed shaft. There is a design of a bearing unit. The bearing unit permits to install and fasten properly the cup-tip tool, and ensure its stable rotation. The article presents a design of a holder for the installation and orientation of the bearing unit. We have selected details, which are not rigid shafts. We have suggested a technique for experimental studies. The essence of the experimental research is reduced to the definition of value of the components of cutting forces and roughness of the surface processed, depending on the angle of crossing and tool axes. According to the results, we have plotted the diagram of dependence of cutting forces and roughness on an angle of crossing. We have determined the optimal angle of crossing of axes of processed and cup-tip tools